Green Synthesis of Silver Nanoparticles using Kayu tulak Leaf (Schefflera Elliptica Harms) Infusion as a Bio-reductant and Its Antibacterial Activity - I Wayan Tanjung Aryasa; Ni Putu Rahayu Artini (Jurnal Kimia Sains dan Aplikasi, 2022)
Metal nanoparticles and exploration of green synthesis can be applied to lung tissue therapy, cancer, and even vaccines. Additionally, due to the rise in microbial resistance or the demand for novel antibiotics, the use of NPs as an antibacterial agent has expanded. Meanwhile, using methods to produce metal nanoparticles based on the abundance of biodiversity as a green-reducing agent will be safer. In the present study, Kayu tulak leaves extract served as the green-reducing agent. The synthesized silver nanoparticles were characterized using a UV-Vis spectrophotometer, PSA (Particle Size Analyzer), and TEM (Transmission Electron Microscope). The results showed that the silver nanoparticles synthesized using Kayu tulak leaf extract at concentrations of AgNO3 1 and 2 mM had absorbance peaks at 436.5 nm and 467 nm, respectively. The average particle size distributions of the two silver nanoparticles were 88.2 and 16.9 nm, respectively. The characterization of silver nanoparticles using TEM obtained a mixture of spherical, hexagonal, and triangular shapes. The silver nanoparticles synthesized using Kayu tulak as a bio-reductant exhibited antibacterial activity. At AgNO3 solutions of 1 and 2 mM, silver nanoparticles showed antibacterial activity against Escherichia coli with inhibition zone diameters of 6.39 ± 0.30 mm and 8.28 ± 0.19 mm (moderate inhibition), while against Staphylococcus aureus were 4.30 ± 0.24 mm (weak inhibition) and 6.39 ± 0.27 mm (moderate inhibition).